??????? ?????? ?? ??? ?????? - Jehad Mohamad Al Hennawy; Zainal Abidin Hajib; Maskanatul Fiqiyah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
Translation is involved in human’s activity and social development and it is an international communication tool between people of different languages and cultures. The Arabs have been aware of the art of translation since ancient times. The Qur'an has discussed on the fact that people are created differently in races, ethnics, languages and customs. Translations are not exclusive to a linguistic activity based on what is said, or what is written, it also includes a complex epistemic and linguistic work. Translations are effective in spreading cultures and civilisation. Arabic language is the identity of those people who express their culture, combine their ideas, which is the indication of a nation's progress and deterioration. Translation is a link in a chain that begins with knowledge acquisition in the first language and ends with culture, through the construction of the intellectual system and the strengthening of its individual and social identity. From the above statement, we are confident that translation plays a vital role in the process of adaptation between different nations and civilizations, as this is still the most sucessful way to integrate one civilisation with another and vice versa; This has played an effective role in the progress of nations, and creates dialogues between different ideas, working to bridge the gap between different civilisations and nations, and strive to expand ideology and develop identity whilst preserving it from deterioration.